Impact of high fasting plasma glucose on liver cancer burden in China: a comprehensive analysis of trends from 1990 to 2021 - Zhan, Zhouwei; Lin, Wei; Yao, Xintong; Huang, Shuqi; Lan, Shuangting; Zheng, Lina; Guo, Zengqing; Chen, Bijuan (Frontiers in Nutrition, 2025)
BackgroundHigh fasting plasma glucose (HFPG), a key metabolic risk factor, has emerged as a major contributor to the global cancer burden, particularly liver cancer. However, little is known about the long-term trends and sex-specific patterns of HFPG-attributable liver cancer in China.MethodsData were obtained from the Global Burden of Disease Study 2021 to estimate the liver cancer burden attributable to HFPG in China from 1990 to 2021. Metrics analyzed included age-standardized mortality rates (ASMR), disability-adjusted life years (DALYs), years lived with disability (YLDs), and years of life lost (YLLs). Joinpoint regression and decomposition analyses were conducted to evaluate temporal trends and contributing factors.ResultsIn 2021, 3,467 deaths and 83,113 DALYs were attributable to HFPG-related liver cancer in China, with males bearing a higher burden than females. Mortality and DALYs peaked in individuals aged 65–69, and age-standardized rates rose with advancing age, especially among men. Between 1990 and 2021, the absolute burden increased, driven by population aging and growth, although age-standardized rates remained relatively stable. Joinpoint regression showed fluctuating trends with recent declines in DALYs and YLLs, especially in females. Compared to global trends, China exhibited more stability in age-standardized rates. Decomposition analysis identified aging as the primary driver of increased deaths, while population growth led the rise in DALYs. Epidemiological changes slightly offset DALYs in women but increased the burden in men.ConclusionDespite stable age-standardized rates, the absolute burden of HFPG-related liver cancer in China has increased due to demographic shifts, with males and older adults disproportionately affected. Targeted interventions addressing metabolic risk factors in aging populations, particularly men, are urgently needed.